Assessment of the Labial Alveolar Bone Thickness Overlying Maxillary Anterior Teeth in Different Age Groups, Genders, and Sides of the Arch: A Cone Beam Computed Tomographic Study (Medical Forum Monthly, 2024)
Objective: To evaluate the thickness of labial alveolar bone at the maxillary anterior teeth region in various age groups and to document the effect of gender and the side of the arch using images obtained by cone-beam computed tomography (CBCT).Study Design: Cross-sectional retrospective study.Place and Duration of Study: This study was conducted at the Radiology Department of Khyber College of Dentistry Peshawar, Pakistan (KCD), from 4th November 2021 to 3rd May 2022.Methods: After the Institutional Review Board (IRB) approval, 350 CBCT images fulfilled the inclusion criteria and were included in the study. The thickness of the labial alveolar bone was measured perpendicular to the long axis of the tooth in a sagittal plane at bone crest level and 2mm, 4mm, and 6 mm apical to CEJ for each tooth in the maxillary anterior region. P ≤ 0.05 was considered as statistically significant.Results: The study included a mean age of 39.0 ± 12.6 years and an age range from 18-60 years. The sample was composed of 37.1% males and 62.9% females. The results revealed a significant increase in labial bone thickness with age, particularly 4 mm apical to the CEJ. Maxillary central incisors exhibited the highest thickness, while lateral incisors had the thinnest labial bone. No significant gender difference was found, but lateral asymmetry was observed.Conclusion: This study reveals age-related changes and regional variations in labial alveolar bone thickness overlying the maxillary anterior teeth. The results emphasize the importance of considering these factors in dental treatment planning to optimize outcomes. Lateral asymmetry emphasizes the need for individualized evaluation of each side during clinical procedures. These insights can guide dental practitioners in making informed decisions for improved treatment and esthetic results.